Performance Evaluation and Scientific Mapping in Sustainability-Focused Green Finance and Literacy - Manpreet Kaur; Babli Dhiman (Anuário do Instituto de Geociências, 2025)
This study presents a comprehensive bibliometric analysis along with a systematic literature review to explore climate finance by addressing two critical challenges of contemporary society: environmental improvement and subjective well-being from a cluster view. This study exported articles from Scopus from 1993 to 2023. Based on Preferred Reporting for Systematic Reviews and Meta-Analysis (PRISMA), 310 articles were carefully analyzed or selected to use advanced bibliometric tools and techniques, such as biblioshiny (R software), to explore this study and verified using Vos viewer software. The results of the performance analysis and scientific mapping reveal that publications on green investment and financial literacy have risen dramatically in the few years since 2020, which can be seen as the effect of COVID-2019 and the Paris Climate Agreement. The scientific publication of word clouds has depicted a significant impact on literacy in the financial market, reducing biases and making sound financial decisions by considering the environment. This study examines green finance, financial systems, and financial literacy to demonstrate the interdisciplinary nature of climate finance research. This holistic approach emphasizes how economic, environmental, and social variables affect sustainability goals. This study informs policymakers and strategic planners to underline green finance for a robust and sustainable economy while making investment decisions. This study focused on the Scopus database up to 2023. Relevant publications from other databases or external factors that influence trends might have been excluded from the analysis.